Study of resonance interactions in polyatomic molecules on the basis of highly accurate experimental data: Set of strongly interacting Bands ν10(B1), ν7(B2), ν4(A2), ν8(B2),ν3(A1) and ν6(B1) of CH2=CD2 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Gromova O. V. Olga Vasilievna; Bekhtereva E. S. Elena Sergeevna; Beryozkin K. B. Kirill Borisovich; Kashirina N. V. Nadezhda Vladimirovna; Tan T. L.; Sydow C .; Maul C .; Bauerecker (Bauerekker) Z. (S.) H. Zigurd (Sigurd) Hermann (2016, 2016)
Title screen